HOW BLOCKCHAIN TECHNOLOGY CAN ENHANCE TRANSPARENCY AND EFFICIENCY IN ACCOUNTING FOR BOTH CRYPTOCURRENCY AND FOREX TRANSACTIONS: https://doi.org/10.5281/zenodo.15527049 - Odilov, Dilshod (Journal of Contemporary World Studies, 2025)
This paper explores the transformative potential of blockchain technology in enhancing transparency, security, and operational efficiency within the accounting practices of cryptocurrency and forex transactions. As global financial markets increasingly embrace digital assets and decentralized systems, traditional accounting methods face challenges in ensuring real-time verification, data integrity, and regulatory compliance. By integrating blockchain, accountants and financial institutions can access immutable transaction records, streamline auditing processes, and reduce fraud risks. The paper analyzes current applications, discusses regulatory implications, and proposes a model for the adoption of blockchain-based accounting systems in digital asset management.